Unpicking the Inter-relationships Between Off-Farm Livelihood Diversification, Household Characteristics, and Farm Management in the Rural Andes - Caulfield, Mark E.; Hammond, James; Fonte, Steven J.; Florido, Miguel Angel; Fuentes, Walter; Meza, Katherin; Navarette, Israel; Vanek, Steven J.; van Wijk, Mark (Frontiers in Sustainable Food Systems, 2021)
Rural households across the world are increasingly turning to off-farm sources of income to complement or replace farm income. A better understanding of these livelihood adaptations, their consequences, and the processes behind them will facilitate more effective rural development policies and projects. The objective of this research was to examine how off-farm income influences rural livelihoods, elucidate factors that determine different livelihood strategies, as well as understand how these livelihood strategies are associated with different approaches to farm management. Using data from 588 Rural Household Multi-Indicator Surveys (RHoMIS) in three rural Andean regions in Bolivia, Ecuador, and Peru, we identified a typology of farming household livelihood strategies, and assessed the differences among these household types with regard to household and farm level characteristics, and farm management. We found that among the household types that incorporated off-farm income into their livelihood strategies, there were significant differences in approaches to farm management. Specifically, we observed an increased use of industrialized farming techniques among one household type, a deintensification, or a stepping-out of farming activities in another household type, and a tendency toward livestock specialization in the other household type. Moreover, our findings revealed that household level characteristics (age and education level of head(s) of household, and household composition) played an important role in mediating which type of livelihood strategy the households employed. For example, “stepping-out” households generally had younger and more educated household heads. Location-specific factors such as access to markets, irrigation, and off-farm employment opportunities were also likely to be highly influential in terms of which pathways farming households adopted as their livelihood strategy. We conclude that rural development programmes and projects must be driven by the rural communities themselves taking into account this heterogeneity in household characteristics and livelihoods and engaging in the already advanced conversations around different approaches to farming and the conservation of common natural resources.